2012
DOI: 10.1111/j.1472-4642.2011.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Designing occupancy surveys and interpreting non‐detection when observations are imperfect

Abstract: Aim Conservation practitioners use biological surveys to ascertain whether or not a site is occupied by a particular species. Widely used statistical methods estimate the probability that a species will be detected in a survey of an occupied site. However, these estimates of detection probability are alone not sufficient to calculate the probability that a species is present given that it was not detected. The aim of this paper is to demonstrate methods for correctly calculating (1) the probability a species o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 35 publications
0
74
0
Order By: Relevance
“…The probability of obtaining 3 nondetections if the site is truly occupied is only 3.6% (i.e., (1 − 0.66) 3 ; McArdle, 1990, Wintle, Walshe, Parris, & McCarthy, 2012, thus the model is unlikely to conclude that sites 2 or 3 are occupied. The probability of obtaining 3 nondetections if the site is truly occupied is only 3.6% (i.e., (1 − 0.66) 3 ; McArdle, 1990, Wintle, Walshe, Parris, & McCarthy, 2012, thus the model is unlikely to conclude that sites 2 or 3 are occupied.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of obtaining 3 nondetections if the site is truly occupied is only 3.6% (i.e., (1 − 0.66) 3 ; McArdle, 1990, Wintle, Walshe, Parris, & McCarthy, 2012, thus the model is unlikely to conclude that sites 2 or 3 are occupied. The probability of obtaining 3 nondetections if the site is truly occupied is only 3.6% (i.e., (1 − 0.66) 3 ; McArdle, 1990, Wintle, Walshe, Parris, & McCarthy, 2012, thus the model is unlikely to conclude that sites 2 or 3 are occupied.…”
Section: Discussionmentioning
confidence: 99%
“…; Wintle et al . ). For example, wildlife management agencies must assess the risk to endangered bats from proposed development projects, such as wind energy projects (U.S.…”
Section: Methodsmentioning
confidence: 97%
“…A number of studies have shown how likelihood and Bayesian methods can be used to calculate the probability that a location is negative given that a non-detection has been observed and use this to inform estimates of population abundance (Tyre et al 2003, Mackenzie and Royle 2005, Guillera-Arroita et al 2010, Wintle et al 2012. Hughes et al (2002), for example, show how for plant pathogens the number of samples required to ensure a FIG.…”
Section: Discussionmentioning
confidence: 99%